Pengembangan Potensi Pariwisata Desa Pengkol - Binarti, Floriberta (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2023)
Tourism is one of the leading sectors in several regions that potentially increase the regional income and open up business opportunities for the surrounding community. As a local and foreign tourist destination, the Special Region of Yogyakarta has many unique tourist attractions that are the main tourists’ attraction. Pengkol Village which is located in Patuk District, Gunungkidul Regency, the Special Region of Yogyakarta has some potential tourist destinations. Through the Kuliah Kerja Nyata which was took place in Pengkol Village, authors proposes to develop the tourism potential of Mount Keruk, Mount Genter and cultural art tourism in Pengkol Village. This tourism development proposal is based on the literature review and secondary data related to the Pengkol Village’s potential, identification of problems, data analysis that narrows to solving tourism development problems. Some of the solutions offered to increase tourist visits are the addition of supporting facilities to increase comfort for the visitors and hold cultural arts performances at tourist sites.